In vitro study of glyphosate effects on thyroid cells. (15th January 2023) - Coperchini, Francesca; Greco, Alessia; Croce, Laura; Denegri, Marco; Magri, Flavia; Rotondi, Mario; Chiovato, Luca
Abstract: Glyphosate is a pesticide, which contaminates the environment and exposes workers and general population to its residues present in foods and waters. In soil, Glyphosate is degraded in metabolites, amino-methyl-phosphonic acid (AMPA) being the main one. Glyphosate is considered a potential cancerogenic and endocrine-disruptor agent, however its adverse effects on the thyroid were evaluated only in animal models and in vitro data are still lacking. Aim of this study was to investigate whether exposure to Glyphosate could exert adverse effects on thyroid cells in vitro . Two models (adherent-2D and spheroid-3D) derived from the same cell strain Fisher-rat-thyroid-cell line-5 (FRTL-5) were employed. After exposure to Glyphosate at increasing concentrations (0.0, 0.1–0.25- 0.5-1.0-2.0–10.0 mM) we evaluated cell viability by WST-1 (adherent and spheroids), results being confirmed by propidium-iodide staining (only for spheroids). Proliferation of adherent cells was assessed by crystal violet and trypan-blue assays, the increasing volume of spheroids was taken as a measure of proliferation. We also evaluated the ability of cells to form spheroids after Glyphosate exposure. We assessed changes of reactive-oxygen-species (ROS) by the cell-permeant H2DCFDA. Glyphosate-induced changes of mRNAs encoding for thyroid-related genes (TSHR, TPO, TG, NIS, TTF-1 and PAX8) were evaluated by RT-PCR. Glyphosate reduced cell viability and proliferation in both models, even if at different concentrations. Glyphosate at the highest concentration reduced the ability of FRTL-5 to form spheroids. An increased ROS production was found in both models after exposure to Glyphosate. Finally, Glyphosate increased the mRNA levels of some thyroid related genes (TSHR, TPO, TG and TTF-1) in both models, while it increased the mRNAs of PAX8 and NIS only in the adherent model. The present study supports an adverse effect of Glyphosate on cultured thyroid cells. Glyphosate reduced cell viability and proliferation and increased ROS production in thyroid cells. Graphical abstract: Image 1 Highlights: Glyphosate reduces cell viability of FRTL-5 thyroid cells. Glyphosate reduces cell proliferation of FRTL-5 thyroid cells. Glyphosate induce ROS production by FRTL-5 thyroid cells. Glyphosate increase the expression of thyroid related genes. Abstract : Capsule: Glyphosate exposure of FRTL-5 modified cell viabilityproliferationROS production and altered thyroid-related gene expression.